2016
DOI: 10.2147/ijn.s120104
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exposure to nanoparticles and nanomaterials on the mammalian epigenome

Abstract: Human exposure to nanomaterials and nanoparticles is increasing rapidly, but their effects on human health are still largely unknown. Epigenetic modifications are attracting ever more interest as possible underlying molecular mechanisms of gene–environment interactions, highlighting them as potential molecular targets following exposure to nanomaterials and nanoparticles. Interestingly, recent research has identified changes in DNA methylation, histone post-translational modifications, and noncoding RNAs in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…Therefore, the interaction of SNPs or silver ions with the other compounds and elements in human saliva should be better evaluated, 64 especially as the increased production of materials containing nanoparticles presents an important toxicological concern. 65,66 The results obtained in the present study showed that the materials modified with SNPs have a time-limited ion release. Similar results were obtained by Ferraris et al 56 Such materials will most probably exhibit antibacterial properties in the first weeks/months after implantation, until the silver concentration provides minimal bactericidal concentrations.…”
supporting
confidence: 51%
“…Therefore, the interaction of SNPs or silver ions with the other compounds and elements in human saliva should be better evaluated, 64 especially as the increased production of materials containing nanoparticles presents an important toxicological concern. 65,66 The results obtained in the present study showed that the materials modified with SNPs have a time-limited ion release. Similar results were obtained by Ferraris et al 56 Such materials will most probably exhibit antibacterial properties in the first weeks/months after implantation, until the silver concentration provides minimal bactericidal concentrations.…”
supporting
confidence: 51%
“…high specific area, the use of nanomaterials increases every year in industrial and technological processes or in medical applications. Despite their exceptional qualities, their deleterious impact on the environment and health also gives rise to an increasing number of publications 1 4 . Among their numerous uses, nanoparticles and particularly metal-oxide nanoparticles, have often been used for their antibacterial properties, reviewed in 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic and genotoxic effects of the nanomaterials have also been widely studied [41][42][43][44][45][46][47][48][49][50]. The Ames assay has been employed to observe Gene mutations in Chinese hamster lung (CHL/IU) cells upon exposure to fullerenes [51].…”
Section: Current Approaches For Toxicological Assessment Of Nanomatermentioning
confidence: 99%